2009
DOI: 10.1111/j.1582-4934.2009.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β2 is specifically expressed in human dermal papilla cells and modulates hair folliculogenesis

Abstract: Dermal papilla cells (DPCs) in the mammalian hair follicle have been shown to develop hair follicles through epithelial–mesenchymal interactions. A cell therapy to regenerate human hair is theoretically possible by expanding autologous human DPCs (hDPCs) and transplanting them into bald skin, though much remains to be overcome before clinical success. In this study, we compared gene signatures of hDPCs at different passages and human dermal fibroblasts, and found transforming growth factor (TGF)-β2 to be highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 77 publications
4
40
0
3
Order By: Relevance
“…1A). Likewise, gene expression of ALPL and TGF-␤2, both related to the hair-inductive capacity of hDPCs [24], was upregulated by VD 3 treatment at 24 -48 hours (supplemental online Fig. 1B, 1C).…”
Section: Vd 3 Effects On Gene Expression Of 24-hydroxylase Alpl Andmentioning
confidence: 89%
See 2 more Smart Citations
“…1A). Likewise, gene expression of ALPL and TGF-␤2, both related to the hair-inductive capacity of hDPCs [24], was upregulated by VD 3 treatment at 24 -48 hours (supplemental online Fig. 1B, 1C).…”
Section: Vd 3 Effects On Gene Expression Of 24-hydroxylase Alpl Andmentioning
confidence: 89%
“…The dermal papilla and lower dermal sheath around the end bulb of a follicle specifically express ALP activity and have the potential capacity to restore hair growth [25]. TGF-␤2 is involved in promotion of the hair placode [16], contributes to anagen induction [45], is highly expressed in hDPCs compared with hDFs, and is suggested to mediate the hair-inductive capacity of DPCs [24]. Wnt10b is known to play crucial roles in fetal development of hair follicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Qiao et al (5) recently demonstrated maintenance of trichogenicity of cultured human DP cells cultured in medium conditioned with keratinocytes of newborn foreskin. In addition, Inoue et al (6) reported that use of conditioned media obtained from culture of human facial skin keratinocytes resulted in preservation of the trichogenicity of human DP cells.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Deficiency symptoms have been described for inadequacy of vitamin supply, which relate to generally well-understood roles in cell biochemistry. These include ribloflavin, niacin, pantothenic acid, folic acid and biotin (general effects on integumental tissues including caprine and sheep hair follicles (Tahmasbi et al, 2007a and2007b;Galbraith 2010)), vitamin A and retinoids, which are essential for cell proliferation and vitamin D that influences TGF b2 upregulation and follicle development (Inoue et al, 2009). Important cations include calcium that provides signal transduction in keratinocytes (Pruche et al, 1996) and magnesium, which has a role in energy-providing phosphate transfer reactions and DNA degradation and synthesis.…”
Section: Nutrientsmentioning
confidence: 99%